Sports and pedagogical improvement in the training of future teachers of physical education - Slastina H.A (Kharkov National Pedagogical University, 2013)
Revealed the structure and content of the sport and improve teaching students of physical education in their chosen sport. The place of discipline and the value of "Sports and teacher improvement" in the preparation of future teachers of physical education. It is shown that the purpose of discipline is to familiarize students with the theoretical foundations and experience teaching and training work in their chosen sport, the methodology of this work with children of different ages. The main forms of teaching attributed lectures, seminars, practical, methodical surveillance, individual, self-study and educational practice. It is noted that discipline is allocated 522 hours. Of these 64 hours - at a lecture, 262 - on practical training, 86 hours - for individual classes, 174 hours - to work independently. A 4th year student provides the implementation of the course work.